Effect of plant growth regulators on coloured callus formation and accumulation of azadirachtin, an essential biopesticide in Azadirachta indica - Ashokhan, Sharmilla; Othman, Rashidi; Abd Rahim, Muhamad Hafiz; Karsani, Saiful Anuar; Yaacob, Jamilah Syafawati (MDPI, 2020)
For centuries, Azadirachta indica or neem has been utilized as a primary source of medicine due to its antimicrobial, larvacidal, antimalarial and antifungal properties. Recently, its potential as an effective biopesticide has garnered attention, especially towards efficient and continuous production of its bioactive compounds. The present study investigated the effect of the plant growth regulators (PGRs) thiadiazuron (TDZ) and 2,4-dichlorophenoxyacetic acid (2,4-D) on the induction of colored callus formation and subsequent accumulation of azadirachtin (AZA) in A. indica. An efficient protocol was established for micropropagation and colored callus production of this species, followed by quantification of AZA (a mixture of azadirachtin A and B) and its safety assessment. For induction of the callus, leaf and petiole explants obtained from a young growing neem plant were excised and cultured on Murashige and Skoog (MS) medium supplemented with TDZ (0.2–0.6 mg L−1) and 2,4-D (0.2–0.6 mg L−1), either applied singly or in combination. Callus was successfully induced from both explant types at different rates, where media with 0.6 mg L−1 of TDZ resulted in the highest fresh weight (3.38 ± 0.08 g). In general, media with a single hormone (particularly TDZ) was more effective in producing a high mass of callus compared to combined PGRs. A culture duration of six weeks resulted in the production of green, brown and cream colored callus. The highest callus weight and accumulation of AZA was recorded in green callus (214.53 ± 33.63 mg g−1 dry weight (DW)) induced using TDZ. On the other hand, small amounts of AZA were detected in both brown and cream callus. Further experimentation indicated that the green callus with the highest AZA was found to be non-toxic (LC50 at 4606 µg mL−1) to the zebrafish animal model. These results suggested that the addition of different PGRs during in vitro culture could prominently affect callus and secondary metabolite production and can further be manipulated as a sustainable method for the production of a natural and environmentally friendly pesticide.